(untitled) (Research, Society and Development, 2021)
Superabsorbent polymers (SAP) have gained the attention of the engineering field for applications in cementitious composites. Recently, many studies have addressed using these materials as an alternative to controlling recurrent pathologies, especially retraction in the hardening stage. This study conducted a literature review in the Scopus and Web of Science databases to identify relevant studies for future research in this area. Analyses were performed using the RStudio software program, where data on the number of publications, the main authors and journals, the most used keywords, and most common countries of publication were analyzed. Furthermore, bibliographic coupling and co-citation analyses were carried out. The results indicate that the most published authors were De Belie, Snoeck and Liu J., and the most cited authors were Jensen, Schrofl and Snoeck. Although Brazil is among the fifteen most published countries, it was not among the most cited, showing lacks in studies. In total, 343 articles were found in the Scopus database and 369 in the Web of Science.